1990
DOI: 10.3354/meps067235
|View full text |Cite
|
Sign up to set email alerts
|

Predation by copepods upon natural populations of Phaeocystis pouchetii as a function of the physiological state of the prey

Abstract: Confl~chng data have been previously presented on the ablllty of copepods to prey upon the prymneslophyte Phaeocystls pouchetu Whde some have suggested that gelatinous colonies of thls species c o n t a n blochemlcal substances that prevent t h e~r consumption others have shown that both slngle cells and colon~es of P pouchetu can serve as an excellent food source The present study presents data from feedlng expenments uslng 4 specles of copepods and natural samples of phytoplankton prey from a south-north tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…This situation seems to be diVerent from the haemolytic glycolipids extracted from P. globosa isolated from ichthyotoxic blooms in Chinese coastal waters (He et al 1999), the glycolipids from the prymesiophyte Chrysochromulina polylepis (Yasumoto et al 1990), or the polyethers found for Prymnesium species , and references therein). Because of the low haemolytic activity of the cell extracts, it is doubtful if predators on P. pouchetii in the mesocosm would experience negative eVects after consumption of this prey, although healthy colonies are avoided by some copepods (Estep et al 1990). Organisms such as bacteria and phytoplankton that co-occur with Phaeocystis, however, may be inhibited by this lytic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation seems to be diVerent from the haemolytic glycolipids extracted from P. globosa isolated from ichthyotoxic blooms in Chinese coastal waters (He et al 1999), the glycolipids from the prymesiophyte Chrysochromulina polylepis (Yasumoto et al 1990), or the polyethers found for Prymnesium species , and references therein). Because of the low haemolytic activity of the cell extracts, it is doubtful if predators on P. pouchetii in the mesocosm would experience negative eVects after consumption of this prey, although healthy colonies are avoided by some copepods (Estep et al 1990). Organisms such as bacteria and phytoplankton that co-occur with Phaeocystis, however, may be inhibited by this lytic action.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial consumption rates of acrylate in Weld samples increased when the > 20 m fraction containing P. globosa colonies was removed (Noordkamp et al 2000). And then there is the so-called legend of Phaeocystis unpalatability (Huntley et al 1987) that says that healthy colonies are not consumed due to some sort of chemical deterrence (Estep et al 1990). The observed negative eVects of Phaeocystis presence on other organisms may be a key to its bloom forming capacity; chemical deterrence could be a way to reduce grazing (Nejstgaard et al, this issue) as well as inhibiting competitors (allelopathy), thereby increasing Wtness.…”
Section: Introductionmentioning
confidence: 99%
“…the literature on the use of Phaeocystis as food for higher trophic levels is contradictory. Some studies indicate that Phaeocystis single ceils and colonies can serve as food for zooplankton; whereas other studies indicate Phaeocystis to be unmfitable fond ~Waisse ~t al.. 1994 and references cited therein), Its suitability as food for copepods can also be dependent on the physiological state of the algae (Estep et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed significant grazing of the copepod genus Calanus on Phaeocystis (Tande & BAmstedt 1987, Hansen et al 1990), whereas others reported low grazing pressure on Phaeocystis by Calanus and other copepod genera (Hansen & van Boekel 1991, Bautista et al 1992. Estep et al (1990) related grazing on Phaeocystis colonies by copepods to the physiological condition of the colonies. Grazing losses of Phaeocystis cells caused by microzooplankton can be substantial (Admiraal & Venekamp 1986, Weisse & Scheffel-Moser 1990.…”
Section: Introductionmentioning
confidence: 99%